2019
DOI: 10.3390/ijerph16091538
|View full text |Cite
|
Sign up to set email alerts
|

The Satisfaction with Life Scale and the Subjective Well-Being Inventory in the General Korean Population: Psychometric Properties and Normative Data

Abstract: This study aims to evaluate the psychometric properties of the Satisfaction with Life Scale (SWLS) and the Subjective Well-Being Inventory (SWBI) in a nationally representative sample in Korea. A total of 1200 people completed the semi-structured, self-reported questionnaire, which included five items from the SWLS and 14 items from the SWBI. All items and the total score of both the SWLS and the SWBI showed high internal consistency (with Cronbach’s alphas of 0.886 and 0.946, respectively). The item-total cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
4
24
3
2
Order By: Relevance
“…This study and past studies' findings [14] suggested that undergraduates that acquire a meaningful life are feeling optimistic about their life. The result also parallels with past studies [13,15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study and past studies' findings [14] suggested that undergraduates that acquire a meaningful life are feeling optimistic about their life. The result also parallels with past studies [13,15].…”
Section: Discussionsupporting
confidence: 91%
“…Acquiring good satisfaction in life has a positive link to social relationships [12]. Past studies found satisfaction with life has a positive relationship with flourishing components such as well-being [13], optimism [14], and self-esteem [15].…”
Section: Satisfaction With Life Academic Performance and Flourishingmentioning
confidence: 99%
“…In Korea, studies about subjective well‐being were began in 2013. A large‐scale study was recently reported to examine LS in normal population . According to the study, the total SWLS score of all subjects was 21.8, and those of subjects over 60 y old were also 21.8, which are somewhat higher than the results of this study.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, we used the Satisfaction With Life Scale (SWLS), an internationally recognised self‐report questionnaire that yields an overall measure of satisfaction (sum of scores on individual life domains) . The scale included five questions that explore LS (including non‐affective subjective well‐being) measured using a seven‐point Likert scale, as follows: (1) In most ways my life is close to my ideal; (2) The conditions of my life are excellent; (3) I am satisfied with my life; (4) So far I have gotten the important things I want in life; and (5) If I could live my life over, I would change almost nothing.…”
Section: Methodsmentioning
confidence: 99%
“…The SWLS and PHQ‐8 are validated survey instruments that have been applied in a variety of general population contexts, as well as in subgroup studies 24,38‐43 . SWLS has been thought to be a stable longitudinal measure of well‐being that was largely immune to external effectors.…”
Section: Discussionmentioning
confidence: 99%